2013
DOI: 10.1093/sf/sot066
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Significance of Cohort and Period Effects in Hierarchical Age-Period-Cohort Models: Applications to Verbal Test Scores and Voter Turnout in U.S. Presidential Elections

Abstract: In recently developed hierarchical age-period-cohort (HAPC) models, inferential questions arise: How can one assess or judge the significance of estimates of individual cohort and period effects in such models? And how does one assess the overall statistical significance of the cohort and/or the period effects? Beyond statistical significance is the question of substantive significance. This paper addresses these questions. In the context of empirical applications of linear and generalized linear mixed-model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…However, the HAPC model is able to assess random variation in periods and cohorts, so long as any trends are absorbed in the fixed part of the model. These may well be of substantive interest, telling us, for example, that baby boomers have a higher level of literacy (a cohort effect), or that voter turnout in America was particularly high in the 1960 election between Kennedy and Nixon (a period effect): both of these results can be interpretations of the examples used by Frenk, Yang and Land (2013) 23 . In both of these cases it seems that the age terms in the fixed part of the model accounted for all APC trends 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the HAPC model is able to assess random variation in periods and cohorts, so long as any trends are absorbed in the fixed part of the model. These may well be of substantive interest, telling us, for example, that baby boomers have a higher level of literacy (a cohort effect), or that voter turnout in America was particularly high in the 1960 election between Kennedy and Nixon (a period effect): both of these results can be interpretations of the examples used by Frenk, Yang and Land (2013) 23 . In both of these cases it seems that the age terms in the fixed part of the model accounted for all APC trends 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Glenn (2005, p. 6) This paper considers one of these solutions, proposed recently by Yang and Land (2006) with some additional methodological caveats discussed in subsequent papers (Frenk, Yang and Land 2013;Yang 2006;. The methodology has already been employed in a number of empirical applications, studying social trends in happiness (Yang 2008a), voter turnout (Dassonneville 2013), obesity (Reither, Hauser and Yang 2009), religious service attendance (Schwadel 2010), and cannabis use (Piontek et al 2012), to name a few.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, social issues may provoke civic engagement independent of cohort changes (Caren, Ghoshal, and Ribas 2011;Frenk, Yang, and Land 2013). Contentious issues are period effects that could generate an outpouring of letters to the editor, contacting elected officials, petition signing, and attendance at public meetings.…”
Section: Potential Confounding Effectsmentioning
confidence: 99%
“…Caren, Ghoshal, and Ribas (2011) also found cohort-level decreases in petition signing and protesting, although they found that the decline started with later cohorts. However, differences in voting behavior are primarily due to period rather than cohort changes (Smets and Neundorf 2014;Frenk, Yang, and Land 2013) ii .…”
mentioning
confidence: 99%